Healthcare receivers’ acceptance of telecardiology in Malaysia - Kee Jiar Yeo; Rania Hussien Ahmed Al-Ashwal; Lina Handayani; Shih Hui Lee (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This quantitative study investigates acceptance towards implementation of telecardiology in Malaysia. The purpose of this study is to explore and understand the potential factors that could be the key elements in cultivating positive behaviour towards telecardiology adoption in Malaysia. Data was gathered by using survey method from 149 patients and publics who use internet service in their daily lives. The questionnaire was developed by integrating Technology Readiness Index (TRI), Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB) which consists of 42 items. Descriptive statistics, factor analysis and one-way ANOVA were conducted to analyse the data. The analysis reveals that Malaysians generally hold a positive perception towards implementation of telecardiology with some reservations. Besides that, gender and income of the respondents were found to influence the variables in telecardiology readiness, hence suggesting these two variables be taken into considerations in the adoption of telecardiology. It is our hope that the result of this study provides some useful information for the policy makers and implementers to develop effective implementation strategies that could reduce users’ resistance and adoption barriers in telecardiology adoption.